Evaluating the structural response of ceramic-metal laminate under ballistic impact / Mohd Suhairil Meon, Muhammad Qmie Delfrin and Juri Saedon - Meon, Mohd Suhairil; Delfrin, Muhammad Qmie (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2024)
Ceramics are widely employed in armor because of their toughness, but their susceptibility to fractures under high-speed impact poses a challenge. To address this gap, a comprehensive investigation using finite element analysis is undertaken. This study aims to understand the combined behaviour of ceramics and backing plates during ballistic impact. Using ABAQUS software, a range of simulations are conducted involving circular ceramics paired with different types of backing plate, considering varying impact energies. The results revealed that the integrity of the ceramic-metal laminate structure is highly dependent on the laminate configurations. From four combinations of hybrid laminates, the combination of boron carbide with Armox 500T as the backing plate produced an outstanding result based on the structural response analysed in this work. The key results obtained provide valuable insights into the response of ceramic-armored configurations, filling a critical knowledge gap.